University libraries and the indispensable changes in Medical Sciences - Maria Elinor Dulzaides Iglesias; Ana Maria Molina Gomez; Yuniet Rojas Mesa (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
This work deals with some aspects related with university libraries as an ideal environment to articulate science, knowledge and culture and the need of reorganization of structures and functions within these institutions. We make reference to the changes in the Higher Educational System, which have an impact in other teaching levels. We discuss the new challenges in information and knowledge management and conditions in Medical Science field to adapt traditional methods to the new environment. We discuss how to support the required transformations to turn libraries into research and educational centres.